2021
DOI: 10.1002/hbm.25456
|View full text |Cite
|
Sign up to set email alerts
|

Distinct effects of prematurity on MRI metrics of brain functional connectivity, activity, and structure: Univariate and multivariate analyses

Abstract: Premature birth affects the developmental trajectory of the brain during a period of intense maturation with possible lifelong consequences. To better understand the effect of prematurity on brain structure and function, we performed blood-oxygenlevel dependent (BOLD) and anatomical magnetic resonance imaging (MRI) at 40 weeks of postmenstrual age on 88 newborns with variable gestational age (GA) at birth and no evident radiological alterations. We extracted measures of resting-state functional connectivity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…Recent studies adopting machine learning methods, have shown that the functional connectivity data (expressed by different metrics) and volume data are able to predict prematurity both in cohorts of newborns (Smyser et al 2016;G et al 2016;Chiarelli et al 2021) and adults (Shang et al 2019) and to classify age in infants aged between 6 and 12 months (Pruett et al 2015).These studies support the view that a functional architecture of the brain exists before birth and constantly evolves, especially during the rst year of life. Changes in functional connectivity of prematurity also manifest in adults, which supports the hypothesis that neurocognitive disorders associated with preterm birth might represent a disease of brain connectivity (J et al 2011).…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…Recent studies adopting machine learning methods, have shown that the functional connectivity data (expressed by different metrics) and volume data are able to predict prematurity both in cohorts of newborns (Smyser et al 2016;G et al 2016;Chiarelli et al 2021) and adults (Shang et al 2019) and to classify age in infants aged between 6 and 12 months (Pruett et al 2015).These studies support the view that a functional architecture of the brain exists before birth and constantly evolves, especially during the rst year of life. Changes in functional connectivity of prematurity also manifest in adults, which supports the hypothesis that neurocognitive disorders associated with preterm birth might represent a disease of brain connectivity (J et al 2011).…”
Section: Introductionmentioning
confidence: 63%
“…In a recent study by Chiarelli et al (Chiarelli et al 2021) the authors examined the effect of prematurity on measures of rs-FC, resting state functional connectivity nodal strength (rs-FCNS), fractional amplitude of low frequency uctuations (fALFF) and regional volume in 90 ROIs covering the whole brain by performing region-based univariate analysis of each metric to explore the association with GA at birth and the spatial consistency across metrics. To this aim they implemented a Machine learning framework using partial least square regression (PLS).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Atlases are commonly used to spatially normalize MRI data for quantification of anatomical volumes and investigation of structural/functional connectivity and cortical macrostructure/ microstructure [45][46][47][48][49] . However, existing infant atlases (Supplementary Table 5 and Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%